2020
DOI: 10.3390/ijms21186569
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasodilator Property of Poly(ADP-Ribose) Polymerase Inhibitor (PJ34) in the Neonatal and Adult Mouse Is Mediated by the Nitric Oxide Pathway

Abstract: The poly(ADP-ribose) polymerase (PARP) inhibitor PJ34 has been reported to improve endothelial dysfunction in the peripheral system. We addressed the role of PJ34 on the vascular tone and vasoreactivity during development in the mouse brain. Blood flows were measured in the basilar trunk using ultrasonography. Cerebral vasoreactivity or vasodilation reserve was estimated as a percentage increase in mean blood flow velocities (mBFV) recorded under normoxia-hypercapnia in control and after PJ34 administration. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Our data indicated that PJ34 was able to increase CBF after ischemia in neonatal mice, as previously described [7]. Fortunately, early establishment of this collateral supply reduced BBB permeability and tissue damage in the rostral brain only.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data indicated that PJ34 was able to increase CBF after ischemia in neonatal mice, as previously described [7]. Fortunately, early establishment of this collateral supply reduced BBB permeability and tissue damage in the rostral brain only.…”
Section: Discussionsupporting
confidence: 87%
“…Pharmacological inhibition of PARP with PJ34 (10 mg/kg) can prevent endothelial dysfunction associated with hypertension and aging [5] or induced by endothelin-1 [6]. In the cerebral vascular system, we recently reported that a single dose of the PARP inhibitor PJ34 (10 mg/kg) is able to increase cerebral blood-flow (CBF) by recruitment of the microvascular vasodilation reserve (without sex effect), and is likely to act on the endothelial function throughout life (with a major effect in the neonatal and adult brain) in the naive mouse [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the mechanisms behind the sex differences in outcomes are unclear. Some studies suggest that testosterone may worsen injury (Hill et al, 2011 ) or that estrogen may have a protective effect (Nematipour et al, 2020 ), while others indicate that sex differences in cell death pathways may favor females (Renolleau et al, 2007 ; Charriaut-Marlangue et al, 2018 ; Bonnin et al, 2020 ). Recently, advanced neuroimaging methods such as magnetic resonance imaging (MRI), diffusion-weighted MRI, and magnetic resonance spectroscopy have been used to quantify brain damage and metabolite abnormalities in HI models at different time points after injury (Zhu et al, 2008 ; van de Looij et al, 2011 ; Huang et al, 2016 ; Xiao et al, 2020 ; Tabacaru et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, neuronal and glial apoptosis in the brain is preferentially caspase-dependent and caspase-independent in females and males, respectively (Renolleau et al, 2008 ; Askalan et al, 2015 ). Knockout of the gene for poly (ADP-ribose) polymerase 1 (Parp-1), an enzyme that is present only in the caspase-independent pathway, showed significant protection against HI injury in males but not in females (Zhu et al, 2006 ; Charriaut-Marlangue et al, 2018 ; Bonnin et al, 2020 , 2021 ). Moreover, inhibition of caspase cleavage in caspase-dependent pathways is neuroprotective in females only (Renolleau et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy controls, PJ34 has been shown to recruit the arteriolar cerebral vasodilation reserve more strongly in neonatal mice than in adult mice, thereby playing a beneficial role during stroke [ 53 ]. Collateral BF may be established either during arterial occlusion or after reperfusion, depending on the age of the animal, and with the recruitment of one or both routes, depending on the experimental procedure.…”
Section: Discussionmentioning
confidence: 99%